1992
DOI: 10.1210/mend.6.9.1331772
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of the human ferredoxin gene through a single promoter which contains the 3',5'-cyclic adenosine monophosphate-responsive sequence and Sp 1-binding site.

Abstract: We have investigated the functional elements involved in cAMP-stimulated transcription of the human ferredoxin gene. Unlike the bovine gene, the human gene lacked a second upstream RNA initiation site as demonstrated by sequence analysis of the exon boundary, lack of upstream RNA, and analysis of the promoter. The presence of a single promoter was determined by testing the ability of various gene segments to drive the expression of the chloramphenicol acetyltransferase gene after transfection into a mouse adre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…[] +pKa the human ferredoxin 5"-flanking region, the same patterns of transcripts were detected as in Y1 cells [1]. The levels of these transcripts, however, were not stimulated by forskolin treatment ( fig.…”
Section: [] Controlsupporting
confidence: 57%
“…[] +pKa the human ferredoxin 5"-flanking region, the same patterns of transcripts were detected as in Y1 cells [1]. The levels of these transcripts, however, were not stimulated by forskolin treatment ( fig.…”
Section: [] Controlsupporting
confidence: 57%
“…In Kin-8 cells, which do not have active PKA, steroidogenic gene expression was impaired [43]. When Kin-8 cells were transfected with the CAT reporter plasmids driven using different lengths of the human ferredoxin 5)-flanking region, the same patterns of transcripts were detected as in Y1 cells [1]. The levels of these transcripts, however, were not stimulated by forskolin treatment ( fig.…”
Section: Presence Of the Sp1-binding Site In Three Steroidogenic Genesmentioning
confidence: 98%
“…We have previously shown that the -76/-62 sequence of the human ferredoxin gene promoter activated transcription [1]. Proteins bound to this -76/-62 sequence were examined using electrophoretic mobility shift assay with Y1 nuclear extract ( fig.…”
Section: Sp1-like Proteins Bind To the -76/-62 Region Of The Human Fementioning
confidence: 99%